Alpha-Ketoglutarate in Low-Protein Diets for Growing Pigs: Effects on Cecal Microbial Communities and Parameters of Microbial Metabolism - Chen, Jiashun; Kang, Baoju; Jiang, Qian; Han, Mengmeng; Zhao, Yurong; Long, Lina; Fu, Chenxing; Yao, Kang (Frontiers in Microbiology, 2018)
Alpha-ketoglutarate (AKG), a critical molecule in the tricarboxylic acid cycle, is beneficial to intestinal functions. However, its influence on intestinal microbiota and metabolism is not fully understood. We investigated the effects of a low-protein (LP) diet supplemented with AKG on cecal microbial communities and the parameters of microbial metabolism in growing pigs. Twenty-seven young pigs (Large White × Landrace) with an average initial body weight of 11.96 ± 0.18 kg were randomly allotted into three groups (n=9): a normal protein (NP) diet containing 20% crude protein (CP); LP diet formulated with 17% CP (LP diet); or LP diet supplemented with 10 g kg-1 of AKG (ALP diet). After a 35-d trial period, the digesta of the cecum were collected to analyze the concentrations of ammonia and short-chain fatty acids (SCFAs). We also performed a microbial analysis. Although no significant differences were found in performance among the diet groups, pigs fed the ALP diet had greater average daily gain (ADG) when compared with those in the LP group. Experimental diet did not affect cecal bacterial richness or diversity, as determined by Chao1 and ACE species richness measures and Shannon and Simpson indices, respectively. The predominant phyla Firmicutes, Bacteroidetes, and Proteobacteria increased in relative abundances in the cecum of pigs fed ALP diet. At the genus level, compared to the LP diet, the ALP diet significantly increased the abundances of Lachnospiraceae UCG-005, Lachnospiraceae NK4A136 group, Phascolarctobacterium and Parabacteroides, while decreased Vibrio and Maritalea. Pigs fed the ALP diet increased Oribacterium and Lachnoclostridium when compared with the NP diet. Nonmetric multidimensional scaling analysis revealed that the distribution of microbiota at each group was distinctly clustered separately along principal coordinate. The ALP diet was associated with increases in the amounts of Bacteroides，Bifidobacterium, and Lactobacillus, but a decrease in the level of Escherichia coli. Compared with the NP diet, the ALP diet enhanced the concentrations of valerate and propionate. This ALP diet also increased the concentrations of valerate and isobutyrate when compared with the LP diet. Moreover, the ALP diet was linked with a significant decline in the concentration of ammonia in the cecum. These